Correlation between arterial stiffness and coronary flow velocity reserve in subjects with pulse wave velocity >1400 cm/s - Liu, Jinbo; Wang, Ying; An, Huijie; Liu, Jia; Wei, Jinru; Wang, Hongyu; Wang, Guang (Clinical and experimental hypertension (1993), 2016)
Brachial-ankle pulse wave velocity (ba-PWV) is an independent predictor for cardiovascular events. Coronary flow velocity reserve (CFVR) provides important information for coronary endothelial function. In the present study, we investigated the possible relationship between PWV and CFVR, especially in subjects with PWV > 1400 cm/s. Seventy five subjects were divided into two groups based on baPWV value (baPWV > 1400 cm/s versus baPWV < 1400 cm/s). PWV and CFVR were measured by Colin VP-1000 apparatus and non-invasive Doppler echocardiography, respectively. Our results showed that CFVR was significantly lower in patients with baPWV > 1400 cm/s than in patients with baPWV < 1400 cm/s (2.57 ± 0.68 versus 3.04 ± 0.73, p < 0.01). baPWV was negatively correlated with CFVR in the entire study group (r = −0.45, p < 0.0001) even adjusting for age, prevalence of diabetes mellitus and systolic blood pressure (r = −0.33, p = 0.044). Moreover, baPWV was markedly negatively correlated with CFVR in patients with baPWV > 1400 cm/s (r = −0.42, p < 0.01). Multiple linear regressions showed that baPWV was independently associated with CFVR in the entire study group (β = −0.702, p < 0.001). Our results showed that large arterial stiffness was negatively correlated with decreased CFVR especially in subjects with baPWV > 1400 cm/s, and baPWV was independently associated with CFVR.